Field evaluation of activated carbon-based soil amendment and greenhouse gas monitoring for sustainable jasmine rice cultivation in central Thailand - Smithtun, Pudit; Siripongdee, Surapong; Sonsupap, Somchai (Edelweiss Applied Science and Technology, 2026)
Sustainable rice cultivation requires field-based strategies that reduce environmental impacts while maintaining crop productivity. This study presents an exploratory field evaluation of activated carbon-based soil amendment formulations combined with greenhouse gas monitoring in jasmine rice cultivation in Nakhon Luang District, Phra Nakhon Si Ayutthaya Province, Thailand. Six treatment-level field plots were evaluated using Khao Dawk Mali 105 rice, including a no-amendment control, urea fertilizer 46-0-0, and activated carbon-based amendments containing 2%, 4%, 6%, and 8% activated carbon. Four 2 m × 2 m subplots within each treatment plot were used as within-plot sampling locations and were not treated as independent field replicates. Greenhouse gases were monitored using a closed chamber method coupled with a GASERA ONE gas analyzer, while heavy metals in soil and white rice grain were analyzed using atomic absorption spectrophotometry. The AC-based amendment 6% treatment showed the lowest observed CH₄ response, whereas the AC-based amendment 4% treatment showed the lowest observed N₂O response and lower Pb and Cr concentrations in white rice grain. The AC-based amendment 8% treatment produced the highest yield at 1,582.53 kg ha-1. These findings provide preliminary field evidence and require confirmation through fully replicated field trials.